2020
DOI: 10.1111/jir.12795
|View full text |Cite
|
Sign up to set email alerts
|

Parent perceptions regarding literacy instruction for students with intellectual disability

Abstract: Background Parents offer a unique perspective as they may view literacy instruction through the lens of its direct impact on their child's daily life. Further, they are likely to provide insight into the interactions between the perceived effectiveness of instruction and their expectations for their child's success. The purposes of the current investigation were to explore perceptions of parents of children with intellectual disability (ID) related to their child's literacy instruction in schools and understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For individuals with intellectual disability (ID), difficulty with reading is both the most frequently identified secondary (preventable or ameliorable) condition and the one their caregivers consider to result in the greatest limitation (Koritsas & Iacono, 2011 ). Findings from a recent survey of 211 parents of school-aged children with ID (Wakeman et al, 2021 ) indicated that 93% considered it very important for their child to learn to read and 85% thought that children who were successful in learning to read would have better life outcomes than children who were not.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals with intellectual disability (ID), difficulty with reading is both the most frequently identified secondary (preventable or ameliorable) condition and the one their caregivers consider to result in the greatest limitation (Koritsas & Iacono, 2011 ). Findings from a recent survey of 211 parents of school-aged children with ID (Wakeman et al, 2021 ) indicated that 93% considered it very important for their child to learn to read and 85% thought that children who were successful in learning to read would have better life outcomes than children who were not.…”
Section: Introductionmentioning
confidence: 99%